Hubungan Antara Beban dan Kualitas Hidup Caregiver Penderita Skizofrenia - Pricilla Kartika; Fathra Annis Nauli; Musfardi Rustam (Universitas Bengkulu, 2023)
The health of people with schizophrenia can decline, so they need caregivers. Demands for meeting the needs of sufferers affect the quality of life of caregivers. This study aims to determine the relationship between burden and the quality of life of caregivers with schizophrenia. This research is of the quantitative type with a correlation design, and the approach taken is cross-sectional. There are up to 58 respondents in the sample of schizophrenia caregivers. The instruments used were the Schizophrenia Caregiver Quality of Life (S-CQOL) questionnaire and the Zarit Burden Interview (ZBI), which were declared valid and reliable. The burden of care and quality of life were found to have a significant relationship in this study (= 0.000; correlation coefficient = -0.778). There is a strong relationship between burden and caregivers' quality of life. Based on the findings of this study, nurses at Puskesmas are advised to combat the decline in caregiver quality of life by providing counseling or education to caregivers of schizophrenia in an effort to improve quality of life.